Demographic and Treatment Analysis of Periosteal Osteosarcoma - Michael C. Larkins (Cancer Reports)
ABSTRACT Background and Aims Periosteal osteosarcoma (PO) is a rare bone cancer that makes up between 1% and 6% of osteosarcomas. No epidemiological survey of the United States has been conducted to study this disease, and most of the literature is limited to single‐center analyses and case reports. We seek to perform the first such assessment. Methods The Surveillance, Epidemiology, and End Results (SEER) Program was queried for patients with primary PO (ICD‐O‐3 code 9193/3). Analysis of demographic, disease, and treatment variables was conducted via Fisher's exact test and 20‐year cause‐specific survival (20y CSS) was assessed via logrank analysis. Results Fifty‐four patients with PO were identified; median age was 20–24 years at diagnosis. Multivariate analysis demonstrated surgery provided 20y CSS benefit (hazard ratio [HR] = 0.08, p = 0.040) while chemotherapy (CTX) did not (p = 0.29); however, given the limited number of events (n = 11), recalculation of Cox regression for each variable demonstrated significance only with race (p = 0.026). Younger patients were more likely to be diagnosed with PO of the appendicular skeleton compared to the axial skeleton (p = 0.038). Mean survival time was greater among patients diagnosed with appendicular PO (16.0 years [14.2, 17.9]) compared to axial PO (10.9 years [9.5, 12.4]). Stage‐stratified survival analysis demonstrated surgery alone was non‐inferior to surgery with the addition of CTX (local disease: p = 0.37; regional disease: p = 0.85). Conclusion Axial PO is associated with decreased mean 20y CSS compared to appendicular PO, though in general, appendicular PO is more common than axial PO. In keeping with current literature, treatment of PO with CTX in addition to surgery should be reserved for high‐risk patients, though its use in the treatment of PO is questionable.